Clinical Signs, Maternal and Neonatal Outcomes Associated with Cerebral Vein Thrombosis during Pregnancy and Postpartum period in Mashhad Ghaem Hospital, 2011-2016 - Arezou Sanaeipour; Atieh Mohamadzadeh Vatanchi; Zahra Rajabpour; Mehrad Majd; Fariba Zemorshidi (Mashhad University of Medical Sciences, 2019)
Introduction: Cerebral vein thrombosis is a rare cerebrovascular disorder. Pregnancy and postpartum are associated with an increased risk of cerebral vein thrombosis due to hypercoagolopathy state. With regard to serious morbidity and mortality and the importance of pregnancy and postpartum period, special attention should be given to this disorder in this period. This study was performed with aim to determine the clinical signs and maternal and neonatal outcomes of cerebral vein thrombosis during pregnancy and postpartum period. Methods: This retrospective study was performed on 30 women with cerebral vein thrombosis during pregnancy and postpartum period in Mashhad Ghaem Hospital from 2011-2016. Data collection tool was a researcher-made questionnaire. Demographic data, initial clinical symptoms, affected sinus, infarct and hemorrhage, and maternal and neonatal mortality were collected. Data were analyzed by SPSS software (version 16) and paired t-test. P < 0.5 was considered statistically significant. Results: Cerebral vein thrombosis was diagnosed in 13 women (43.3%) during pregnancy and in 17 (56.7%) during postpartum period. Primary manifestation in more than half of patients was headache (57.7%). The upper sagittal sinus was the most common (70%) and the right sigmoid sinus was the rarest involved sinus (16.6%). Among patients with cerebral vein thrombosis, 4 patients and one fetus died that all 4 patients had hemorrhagic infraction. Conclusion: Considering the importance of pregnancy and postpartum period, rapid diagnosis and timely treatment of cerebral vein thrombosis, especially pay attention to the symptom of headache, is important to improve the prognosis.